Fractal analysis of pore characteristics and their impacts on methane adsorption of coals from Northern China. (2015) - Li, Ziwen; Lin, Baiquan; Gao, Yabin; Cao, Zhaodan; Cheng, Yanying; Yu, Junyang
To better understand the pore characteristics of coal and their impacts on methane adsorption, we have conducted fractal analyses on eight coal samples from Northern China. Results show that the two fractal dimensions have different impact on methane adsorption: D1 has a positive effect on Langmuir volume while D2 has an opposite effect. Langmuir pressure Pl decreases with increasing D1, however, there is no relationship between Pl and D2 . The relationships between pore size distribution and methane adsorption show that both transitional pores and micropores are favourable for methane adsorption reflected in the positive effects on Langmuir volume Vl while only micropores especially pores with diameter smaller than 1.5 nm have significant influence on Langmuir pressure Pl . The relationship between coal rank and Langmuir volume Vl is characterised by a U-shaped curve, with minimum values at medium coal rank (1.0 < Ro, max < 1.5), whereas the Langmuir pressure Pl decreases with increasing coal rank. [Received: June 24, 2013; Accepted: February 19, 2014]